Fundamentação filosófica do princípio do mutualismo nos contratos de seguro - Rodrigues, Vera Maria de Carvalho Pinto (2010)
This essay intends to analyze the principle of mutualism in light of the eighteenth century contractual theory produced by Jean-Jacques Rousseau, as a form of free association that brings benefits for all of its members, which benefits are to be reached through the gathering of forces of those members aiming the common good. It will be explored the similarities between the contractual theory of Rousseau and the principle of mutualism, since in both cases the members of a collectivity contribute to get benefits from this association. Thus, these members assure protection against occasional misfortunes and related damages arising from its occurrence. Then, we start to view the social pact as a more specific kind of association, as in the insurance agreements, and not as a political organization. We will also study the relation between the risk inherent to the social contract and to the insurance agreement, which has the principle of mutualism as cornerstone. It will be discussed the philosophical fundaments of the principle of mutualism in the insurance agreements, since the insurance agreements are based on the concepts of the common good, presented in Rousseau's contractual theory; allowing that all the members of the insured collectivity benefit from the tranquility of having their personal or material assets protected against future or uncertain misfortunes, or against damages caused at the time of the loss, that could not be borne by them individually. At last, we will analyze the principle of mutualism and the insurance agreements in the Civil Code of 2002, and on recent decision of the Appellate Courts of the State of São Paulo